Chemotherapeutic Risk lncRNA-PVT1 SNP Sensitizes Metastatic Colorectal Cancer to FOLFOX Regimen - Wu, Shenshen; Yang, Xi; Tang, Weiyan; Familiari, Giuseppe; Relucenti, Michela; Aschner, Michael; Li, Xiaobo; Chen, Rui (Frontiers in Oncology, 2022)
Recent studies have identified that long noncoding RNA (lncRNA) might affect the responses to anticancer drug treatment, including colorectal cancer (CRC). However, the association between single-nucleotide polymorphisms (SNPs) in PVT1 and the chemotherapy response in metastatic colorectal cancer has yet to be clarified. In this study, the PVT1 rs2278176 CT/TT genotypes were found to be associated with an increased overall survival (OS) and progression-free survival (PFS) compared with the CC genotype. Furthermore, patients harboring the rs2278176 CT/TT genotypes had a greater chance of achieving clinical benefit from 5-Fluorouracil/leucovorin combined with oxaliplatin (FOLFOX). In vivo nude mice experiments demonstrated that the CRISPR/Cas9 mediated rs2278176 C to T mutation significantly inhibited the tumorigenesis of colorectal cancer cells treated with 5-Fu, but not control DMSO treated cells. Furthermore, the apoptotic rate was significantly enhanced by treatment with 5-Fu in the CRC cells carrying with the CT/TT genotypes. Functional studies demonstrated that the PVT1 rs2278176 C to T mutation altered the binding site for hsa-miR-297, and that hsa-miR-297 downregulated Glutathione S-Transferase Alpha 2(GSTA2), a member of phase II detoxification enzyme, in an Argonaute 2(Ago2)-dependent manner. Moreover, GSTA2 levels were downregulated in the cancer tissues of patients carrying rs2278176 CT/TT genotypes. High GSTA2 expression predicted poor clinical outcome in metastatic colorectal cancer treated with FOLFOX. In conclusion, this study provided that PVT1 with rs2278176 T allele altered the binding affinity with hsa-miR-297, leading to decreased GSTA2 expression and sensitized CRC cells to FOLFOX chemotherapy, suggesting rs2278176 CT/TT genotypes might serve as a predictive biomarker to improve prognosis in patients with metastatic CRC treated with FOLFOX.